Environmental Insights Integrated Learning: Strengthening the Ecco-Bhinneka Attitude of Elementary School Students - Patriana, Wendy Dian; Anif, Sofyan; Sutopo, Anam; Narimo, Sabar; Murtiyasa, Budi; Prayitno, Harun Joko; Fauziati, Endang (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: The research objectives of this article are twofold. 1) Exploring Pancasila learning integrated with environmental insight to strengthen the ecco-bhinneka attitude of elementary school; and 2) Identifying learning outcomes of elementary school student’s ecco-bhinneka attitudes. Methodology: The type of research in this article is qualitative. Data collection techniques in this article are interviews with principals and teachers, observation, and documentation. The participants in the study were 21 fourth grade students, 2 teachers, and the principal. Data validity using source and method triangulation. The data analysis technique is inductive data analysis process, namely data collection, data reduction, data display, verification and conclusion. Results: The research results are twofold. 1) Learning is carried out in steps namely gathering information about the theme of discuss and building identity in diversity. Environmental issues are used as starting point to introducing the diversity in everyday life. Reflection on the results of student observations is focused on forming the competency of practicing (A5) ecco-bhinneka attitude. 2) The results of learning carried out by students have criteria for organizing information (A4) about the attitude of ecco-bhinneka which is shown by the results of group discussion. Practicing competence (A5) is shown by students becoming aware that respecting differences is very important in society to maintain environmental balance. Applications/Originality/Value: The study focuses on integrating Pancasila learning with environmental insight, emphasizing the importance of strengthening the eco-bhinneka attitude. This research provides insights into the process of instilling an eco-bhinneka attitude in students and highlights its significance in maintaining environmental balance in society. It contributes to understanding how these values can be incorporated into elementary school education.